Ezy can crusher / Muhammad Na’im Zulfaqar Asmadi Ahmad ...[et al] - Asmadi Ahmad, Muhammad Na’im Zulfaqar; Rosli, Muhammad Wafiq; Abd Rahman, Nur Aireen Nabilah; Mokhtar, Nur Azimah; Zahir Hussein, Zahirul Hazmi
A Can Crusher model that operates manually has been created successfully by using SolidWorks. This prototype is done with the help of mechanical equations which are shaft, torque, shear force, bending moment, and others. This machine requires the user to use their leg to start moving the operation of crushing cans. This machine is also different in equipment used from the current model. This machine was created to increase the quality of fresh air in the surroundings. By using this machine, the number of cans that are thrown without being smashed properly can be reduced. Thus, the aim of this project to save the environment is achieved. As mentioned before, users need to apply force to the pedal by using their energy which is their leg. The force will then distributed to the handle of the pedal and the crank will move with the help of a chain. Lastly, the can will be crushed into the storage. The machine is affordable as it does not require any automated device such as a motor. Using leg helps human to boost energy to instead of doing a heavy exercise.